Grid computing the new frontier of high performance computing - Grandinetti, Lucio, 1941- (Advances in parallel computing, 2005)
The book deals with the most recent technology of distributed computing. As Internet continues to grow and provide practical connectivity between users of computers it has become possible to consider use of computing resources which are far apart and connected by Wide Area Networks. Instead of using only local computing power it has become practical to access computing resources widely distributed. In some cases between different countries in other cases between different continents. This idea of using computer power is similar to the well known electric power utility technology. Hence the name of this distributed computing technology is the Grid Computing. Initially grid computing was used by technologically advanced scientific users. They used grid computing to experiment with large scale problems which required high performance computing facilities and collaborative work. In the next stage of development the grid computing technology has become effective and economically attractive for large and medium size commercial companies. It is expected that eventually the grid computing style of providing computing power will become universal reaching every user in industry and business. * Written by academic and industrial experts who have developed or used grid computing * Many proposed solutions have been tested in real life applications * Covers most essential and technically relevant issues in grid computing.